Inventarisasi potensi emisi metana (CH4) pada peternakan sapi perah di Kecamatan Pujon, Kabupaten Malang - Ali Mahmud; Ari Prima (Universitas Sebelas Maret, 2021)
Objective: The methane emissions in ruminants such as dairy cows was one of the causes of climate change. The aimed of this study was to make an inventory of methane emissions from dairy farms in Pujon District. The methane emission data inventory was expected to assist the government in making policies as an effort to mitigation of methane emissions.Methods: The secondary data used in this study were obtained from journals, books, literature related to research, and data from the Central Statistics Agency (BPS). Methane emissions was calculated using the Tier 1 method according to IPCC reference. The reason for the inventory using the tier 1 method was caused that the specific data related to emissions on dairy cows in Malang Regency were not available. The data obtained were processed descriptively.Results: The data obtained shown that the population of dairy cows in Pujon District from 2013-2015 has increased, in 2016 it experienced a significant decline, namely 14.2%, then from 2017-2019 it continued to decline. Methane emissions from enteric fermentation from 2013-2019 averaged 23.13 Gg CO2-eq / year. Methane emissions from manure management in dairy cows in Pujon District from 2013-2019 were an average of 11.75 Gg CO2-eq / year. The highest methane emissions were in 2015, and the lowest was in 2019.Conclusions: Based on the results of the study, it can be concluded that methane emissions from dairy cows in Pujon District increased from 2013-2015, there was a significant reduction in emissions in 2016 – 2019. Feeding with balanced nutrients, using ingredients of concentrated and forage containing good nutrients quality is an effort to mitigate methane that can applied by farmers.